CHEMISTRY ICT AND LABORATORY EQUIPMENT MANIPULATIVE SKILL TRAINING FOR CHEMISTRY TEACHERS IN EAST AGAM - Miftahul Khair; Budhi Oktavia; Guspatni Guspatni; Tarmizi Tarmizi (Ta'dib, 2011)
In general, schools in eastern Agam Regency have not yet making use optimal computer technology in learning process. Furthermore, limited innovation has been made dealing with the limitation of chemical laboratory work materials. To answer the problem, training on making use of ICT in Chemistry subject and manipulative skill laboratory equipments for Chemistry teachers throughout eastern Agam Regency was conducted.Kata kunci: ICT, manipulative skill, laboratory